Tantangan Dan Peluang Dalam Implementasi Sistem Pajak Online Di Indonesia - Dini Vientiany; Maysa Chairani; Miratul Imaniah; Nurhidayah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the factors that influence the level of taxpayer compliance in using the online tax system in Indonesia, evaluate the effectiveness of the online tax system in Indonesia, and develop strategies to overcome challenges in implementing the online tax system in Indonesia. This research uses a library research or document analysis approach to examine and analyze the challenges and opportunities in implementing the online tax system in Indonesia. This approach was chosen because it allows researchers to explore information that is available from various credible sources. The data collected comes from scientific journals which discuss online tax systems, taxpayer compliance, tax literacy, and the effectiveness of information systems. The online tax system in Indonesia presents significant opportunities to increase taxpayer compliance, tax administration efficiency, and state revenues. However, its implementation faces several challenges, such as limited infrastructure, lack of tax literacy, and suboptimal system security. Strategic efforts to overcome these challenges including internet infrastructure development, education and socialization of tax literacy, increasing system security, and intensifying socialization of the online tax system.